2018
DOI: 10.1093/sysbio/syy011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Molecular Species Delimitation Across a Range of Speciation Scenarios

Abstract: Species are fundamental units in biological research and can be defined on the basis of various operational criteria. There has been growing use of molecular approaches for species delimitation. Among the most widely used methods, the generalized mixed Yule-coalescent (GMYC) and Poisson tree processes (PTP) were designed for the analysis of single-locus data but are often applied to concatenations of multilocus data. In contrast, the Bayesian multispecies coalescent approach in the software Bayesian Phylogenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
261
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(277 citation statements)
references
References 84 publications
8
261
1
7
Order By: Relevance
“…Among them, the results of ABGD and BPP supported 3 species in the L. edwardsi complex, while the result of bPTP supported 5 species. However, bPTP tends to overestimate recognized species (Zhang et al 2013), and is more sensitive than BPP to the effects of gene flow and potential confounding factors (Luo et al 2018). Given appropriate priors and correct guide trees, BPP shows lower rates of species overestimation and underestimation, and is generally robust to various potential confounding factors except high levels of gene flow (Ence & Carstens 2011;Camargo et al 2012;Hime et al 2016;Luo et al 2018).…”
Section: Molecular Species Delimitationmentioning
confidence: 99%
“…Among them, the results of ABGD and BPP supported 3 species in the L. edwardsi complex, while the result of bPTP supported 5 species. However, bPTP tends to overestimate recognized species (Zhang et al 2013), and is more sensitive than BPP to the effects of gene flow and potential confounding factors (Luo et al 2018). Given appropriate priors and correct guide trees, BPP shows lower rates of species overestimation and underestimation, and is generally robust to various potential confounding factors except high levels of gene flow (Ence & Carstens 2011;Camargo et al 2012;Hime et al 2016;Luo et al 2018).…”
Section: Molecular Species Delimitationmentioning
confidence: 99%
“…MtDNA COI sequences were processed with manual assessment of ambiguous base calls with Geneious Pro v.5.6.4 (Kearse et al, 2012) and then aligned using mafft v.6.814 (Katoh, Misawa, Kuma, & Miyata, 2002). In order to define molecular OTUs, we explored Bayesian Inference (BI) and Maximum likelihood (ML) approaches to build trees and different delimitation methods (GMYC, mPTP and a clustering threshold of 96% similarity) to account for their inherent limitations (Luo, Ling, Ho, & Zhu, 2018). First, all sequences for each genus were used to infer ML trees using maximum likelihood in RaxML (Stamatakis, Hoover, & Rougemont, 2008) with a GTR+G substitution model (4 categories).…”
Section: Sequence Alignment and Molecular Otu Delineationmentioning
confidence: 99%
“…The Bayesian coalescent method of BPP is designed to analyse multiple loci and has proven to be efficient in species delimitation (Leaché et al, ; Yang, ; Yang & Rannala, ) and may better reflect observations of morphological divergences (Hurtabo‐Burillo, May‐Itzá, Quezada‐Eúan, Rúa, & Ruiz, ; Lin, Stur, & Ekrem, ; Yang & Rannala, ). In this study, the BPP method fully supported the seven species, and all the nodes had perfect posterior probabilities for all three combinations of the ancestral population size ( θ ) and the root age ( τ 0 ), which indicated that BPP could yield high posterior probabilities for correct species delimitations when appropriate priors were chosen (Luo et al, ; Yang, ; Yang & Rannala, ).…”
Section: Discussionmentioning
confidence: 62%
“…In recent years, the employment of molecular‐based delimitation methods has made great contributions to the defining of species boundaries, especially in morphologically conserved groups (Bluemel et al, ; Chan et al, ; Devitt, Wright, Cannatella, & Hillis, ; Fujisawa & Barraclough, ; Yang, ). Molecular species delimitation can provide preliminary taxonomic hypotheses and valuable complements to morphological taxonomy (Huang et al, ; Luo, Ling, Ho, & Zhu, ). However, defining a new species when relying solely on molecular information is inadequate.…”
Section: Introductionmentioning
confidence: 99%